Comparison of Widal Test Using Serum and Plasma Samples - Rizqoh, Debie; Roina Sitanggang (Fakultas Kedokteran Universitas Sriwijaya (Faculty of Medicine, Universitas Sriwijaya) Indonesia, 2021)
The widal test is a test for diagnostic of thyfoid fever serology. Widal test aims to detect the presence of antibodies against Salmonella antigen, by measuring the degree of agglutination of antibody titer to antigen O and H in sample. In this research Widal test was performed using serumand plasma samples. This study aims to determine whether there is a difference in the value of titer on the Widal test between serum samples and plasma EDTA samples. This type of research is an experimental study. Samples were taken from patient suspected of thyfoid fever of 10 sample in the Laboratory of SM Raja Amplas in 2018. The result of comparative titer Widal test using serum and plasma samples obtained results 30% of the 10 samples examined there are differences in the value of Widal titer but does not affect the final diagnosis of typhoid fever. The value of the Widal test titer using plasma is lower than the value of Widal Titer with the serum samples. The use of plasma samples to determine the Widal titer is particularity susceptible to mingling with the erythrocytes due to the presence of anticoagulant particles but does not affect the result of the Widal test. EDTA anticoagulants do not damage the antibodies contained in the serum, this can be seen in the results of the study, there were no differences in each sample examined, so the difference in results obtained due to other factors, namely the error of researchers in the Widal test. The Widal test using serum samples can gives results according to the actual circumstances because serum is not contaminated by EDTA anticoagulants.